The established and the challenger: A direct comparison of current cryoballoon technologies for pulmonary vein isolation. (18th November 2021) - Moser, Fabian; Rottner, Laura; Moser, Julia; Schleberger, Ruben; Lemoine, Marc; Münkler, Paula; Dinshaw, Leon; Kirchhof, Paulus; Reissmann, Bruno; Ouyang, Feifan; Rillig, Andreas; Metzner, Andreas
Abstract: Introduction: Cryoballoon (CB) ablation for pulmonary vein isolation (PVI) is an effective treatment of atrial fibrillation (AF). Recently, a novel cryoablation system was introduced. The aim of the study was to compare the safety, efficacy and biophysical characteristics of a novel cryoablation system (POLARx™; Boston Scientific) to a commonly used and clinically well characterized system (Arctic Front Advance Pro™, AFA; Medtronic). Methods and Results: Fifty consecutive patients with symptomatic AF, who underwent CB‐based ablation with the POLARx were compared to 50 consecutive patients treated with the AFA. Acute PVI was achieved in 99.8% (POLARx 99.5%, AFA 100%, p  = 1.00). Time to isolation (TTI) was comparable in both groups (POLARx 35 [27, 48] s, AFA 30 [21, 43] s, p  = 0.165). The POLARx showed a lower balloon temperature at TTI (POLARx −44 [−50, −36] °C, AFA −31 [−38, −21] °C, p  < 0.001) and lower nadir temperature (POLARx −60 [−65, −55] °C, AFA −48 [−54, −45] °C, p  < 0.001). Procedure time (POLARx 80 [60, 105] min, AFA 62 [42, 80] min, p  < 0.001), fluoroscopy time (POLARx 17 [13, 22] min, AFA 11 [7, 16] min, p  < 0.001) and freeze cycles per patient (POLARx 5 [4, 6], AFA 4.5 [4, 5], p  = 0.002) were higher in the POLARx group. Two cerebral ischemic events occurred in the POLARx group, two patients in each group had phrenic nerve injury. Conclusion: Both systems enable effective isolation of pulmonary veins. The POLARx required longer procedure and fluoroscopy times. Larger, prospective and randomized studies are needed to assess long‐term efficacy and safety of this technology.